Analisis Kemampuan Representasi Matematis ditinjau dari Self Efficacy pada Siswa Kelas VIII MTs Negeri 2 Mataram Tahun Ajaran 2024/2025 - Elanda, Eva; Subarinah, Sri; Salsabila, Nilza Humaira (FKIP Universitas Mataram, 2025)
Mathematical representation ability is an essential aspect of solving mathematical problems, particularly in the topic of relations and functions. However, in practice, many students struggle to express mathematical ideas through verbal, visual, and symbolic representations. One factor that may influence this ability is self efficacy, or students’ belief in their ability to complete mathematical tasks. This study aims to describe students’ mathematical representation ability in solving problems on relations and functions viewed from their self efficacy. The research was conducted at MTs Negeri 2 Mataram in the academic year 2024/2025 using a descriptive qualitative method. The subjects consisted of three eighth-grade students representing high, moderate, and low self efficacy categories based on questionnaire results. The instruments used included a self-efficacy questionnaire, a mathematical representation test, and interview guidelines. The findings show that students with high self-efficacy were able to fulfill all types of representation accurately and completely. Students with moderate self efficacy showed partial ability but were inconsistent. Meanwhile, students with low self-efficacy experienced difficulties in all forms of representation. These findings indicate a tendency that self efficacy plays a role in students’ quality of mathematical representation ability.